Effect of a Cu seed layer on electroplated Cu film - Pan, Yan; Liu, Yuhong; Wang, Tongqing; Lu, Xinchun (Microelectronic engineering, 2013)
[Display omitted] ► The morphology of the electroplated Cu films is influenced by the Cu layers. ► The hardness of the electroplated Cu film is influenced by Cu seed layer. ► The Cu film adhesion is influenced by Cu seed layer. ► The Cu film is less corrosion-resistant when its roughness value is higher. Cu films with different thicknesses were electroplated onto Cu seed layers. Cu seed layers with different thicknesses were sputtered on a Ta barrier layer; the thickness of Cu seed layer was varied by changing the sputtering time. To investigate the influence of the Cu seed layers on the performance of the electroplated Cu films, the morphology, grain size, crystallographic orientation, and mechanical and chemical properties of the electroplated Cu films are presented in this paper. As the thickness of the Cu seed layer increases, the grain size increases, and the surface morphology changes from flat to rough to smooth. The adhesion of the Cu seed layers to the substrate increases with increasing thickness of the Cu seed layers but eventually decreases. After the electroplated Cu films are deposited, the morphology, grain size, and crystallographic orientation of the electroplated Cu films are significantly influenced by the seed layers. The hardness of the electroplated Cu film increases with the thickness of the Cu seed layer, and finally reaches a constant value. The adhesion between the Cu film and the substrates is influenced by the Cu seed layer as indicated by the morphology of the film. The Cu film is less corrosion-resistant when its roughness value is higher. Better mechanical and chemical properties are obtained when the thickness of the Cu seed layer is 150nm.